Effectiveness of Government Communication in Delivering Public Policy on Social Media - Dwi Siyamsih; Muhamat Arif Afandi; Ihsan Suri (Journal of Dialogos, 2025)
This study aims to analyze the effectiveness of government communication in conveying public policies through social media. The method used is a descriptive qualitative approach with data collection techniques in the form of content analysis of official social media accounts of government agencies, in-depth interviews with key informants, and online observation of public involvement. The results of the study indicate that the effectiveness of government communication on social media still varies between agencies, influenced by communication strategies, language styles, and forms of content presentation. Policy messages are often delivered formally and less communicatively, so they are not fully understood by the public. Two-way interaction is also still limited, resulting in low responsiveness to public comments and questions. Supporting factors for communication effectiveness include the professionalism of the management team, consistency of uploads, and the use of attractive visual content. Meanwhile, the obstacles faced include low digital literacy of the apparatus, limited communication budget, and the absence of standard digital communication guidelines. This study recommends the need for a more humanistic and participatory communication approach so that the delivery of public policies can be more effective and impactful.